2022
DOI: 10.1007/s11628-021-00476-3
|View full text |Cite
|
Sign up to set email alerts
|

Recovering from the COVID-19 shock: the role of risk perception and perceived effectiveness of protective measures on travel intention during the pandemic

Abstract: The COVID-19 pandemic has caused severe damage to the global tourism industry. However, there is hope that the industry will recover in the near future. This study investigates how the pandemic has affected the peoples’ traveling intention and provide implications for accelerating the recovery of the industry. A PLS-SEM analysis of 382 samples confirms the significant effect of COVID-19 risk perception on travel intention while also highlighting the mediating role of perceived effectiveness of COVID-19 protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Furthermore, the result of a recent study shows that perceived risk negatively affects the tourist decision to visit during the COVID-19 Pandemic (Zainuddin et al, 2022). Correspondingly, the study found that COVID-19 risk perception related factors Perceived avoid the ability of COVID-19, Perceived susceptibility to COVID-19, Perceived severity of COVID-19 significant negatively associated with travel intention during pandemic (Yoo et al, 2022). Mental well-being perceived uncertainty negatively affecting tourist travel behavior over a short period or long term period (Chua et al, 2020).…”
Section: Barrier Of Tourist Behaviormentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, the result of a recent study shows that perceived risk negatively affects the tourist decision to visit during the COVID-19 Pandemic (Zainuddin et al, 2022). Correspondingly, the study found that COVID-19 risk perception related factors Perceived avoid the ability of COVID-19, Perceived susceptibility to COVID-19, Perceived severity of COVID-19 significant negatively associated with travel intention during pandemic (Yoo et al, 2022). Mental well-being perceived uncertainty negatively affecting tourist travel behavior over a short period or long term period (Chua et al, 2020).…”
Section: Barrier Of Tourist Behaviormentioning
confidence: 83%
“…We found that most of the empirical research was carried out in Indonesia (n 5 12) (Afriani and Sugiarto, 2020;Alwi et al, 2022;Azis et al, 2020;Bustan and Setiawan, 2021;Kadir et al, 2020;Lemy et al, 2020;Pinem et al, 2021;Sianipar et al, 2021;Sihotang and Sukaatmadja, 2021;Sitinjak et al, 2021;Sukaatmadja et al, 2022;Zainuddin et al, 2022). After that, 7 studies were based on the data collected from China (Agyeiwaah et al, 2021;Cai et al, 2021a;Han et al, 2021;Hu and Xu, 2021;Jiang et al, 2022;Riestyaningrum et al, 2020;Zeng and Li, 2021) followed by the Malaysia (n 5 5) (Ahmad et al, 2021a, b;Hanafiah et al, 2021;Ramli et al, 2021;Tiam Chin et al, 2021) and India (n 5 4) (Gupta et al, 2021;Kour et al, 2021;Rather, 2021a, b) and in Korea (n 5 4) (Shin et al, 2022;Sinha and Nair, 2021;Yoo et al, 2022;Yu et al, 2021). We also noted that three studies were conducted in the USA context (Chua et al, 2020(Chua et al, , 2021Milman et al, 2020;Rasoolimanesh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second part measured CFU using four items from Ahorsu et al (2022) and Yang et al (2022). The third section examined visit intentions using three items from Yoo et al (2022). The fourth segment examined DI using eight items from Hamdy et al (2023a).…”
Section: Methodsmentioning
confidence: 99%
“…Since tourism is impacted by several external factors, the tourism industry is significantly vulnerable to large-scale risks (RITCHIE -JIANG 2019). Travel risk refers to the possibility of experiencing certain forms of threat while travelling, whereas perceived travel risk is often defined as travellers' perceptions of uncertain outcomes of the travel decision or the negative consequences of purchasing the tourism product (PARK -REISINGER 2010, SOHN et al 2016, YOO et al 2022). In the field of travel risk perception, risk associated with international travel is often related to terrorism, war and political instability, health concerns, natural disasters, and acts of crime.…”
Section: Risk Perception In the Tourism Industrymentioning
confidence: 99%